ASEAN Non-Interference Under Heavy Pressure: Is It Change or Crises for ASEAN Peace? - Spastyono, Jeko; Malik, Ichsan; Wahyudi, Bambang (Jurnal Hubungan Internasional, 2024)
This paper intends to join the discussion over the heavily pressured ASEAN's non- interference. With a qualitative approach, this paper investigate where the pressure comes from and whether non-interference actually harms ASEAN. Utilizing the medical analogy, "the dose makes the poison,” and Acton's wisdom on power, the paper argue that the non-interference harm and critics inducing to ASEAN is a result of its excessive uses rather than the principle itself harmful. Avoiding, delaying, and brushing issues aside behind non-interference becomes a comfortable refuge for ASEAN when faced with difficult challenges. ASEAN indeed needs to change. However, given ASEAN's diverse political, cultural, and language differences, eliminating non-interference influence in ASEAN is an outrageous deliberation. The principle is not poisonous with the right prescription. Therefore, as conclusion the paper advocate the creation of a formal forum that can serve as a formal means to brainstorm solutions for members' taboo predicament that could preserve member states freedom to decide, rather than dictating one, to control the dosage of non-interference needed in the ASEAN system. Like a family, ASEAN member states can use the forum to convince each other's that there are better solutions for their predicament and advance the region together.